1965
DOI: 10.1111/j.1748-1716.1965.tb04173.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Clearances of Inulin, Polyfructosan‐S and a Polyethylene Glycol (PEG 1,000) in the Rat

Abstract: Berglund, F. Renal clearance of inulin, polyfructosan‐S and a polyethylene glycol (PEG 1,000) in the rat. Acta physiol. scand. 1965. 64. 238–244. The renal clearances of inulin, polyfructosan‐S and PEG 1,000 were measured in the rat by means of a constant infusion technique. The inulin/PEG 1,000 clearance ratio in 10 rats averaged 0.81, and polyfructosan‐S/PEG 1,000 ratio in 10 rats averaged 0.87. The clearance ratios differed signicantly from unity and were not influenced by phlorizin. The restricted filterab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

1975
1975
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 23 publications
0
10
2
Order By: Relevance
“…PMMA, a nontoxic, nonbiodegradable polymer, has high levels of biocompatibility, which expanded its application in the biomedical field from orthopedics to wound‐dressing manufacturing . PEG, a FDA‐approved water‐soluble polymer, has frequently been used in tissue engineering, drug delivery, and surface modification of medical devices because of its biocompatibility and nonimmunogenicity . Low molecular weight PEG is rapidly cleared from the plasma by kidney, which makes the application of this polymer quite safe …”
Section: Resultsmentioning
confidence: 99%
“…PMMA, a nontoxic, nonbiodegradable polymer, has high levels of biocompatibility, which expanded its application in the biomedical field from orthopedics to wound‐dressing manufacturing . PEG, a FDA‐approved water‐soluble polymer, has frequently been used in tissue engineering, drug delivery, and surface modification of medical devices because of its biocompatibility and nonimmunogenicity . Low molecular weight PEG is rapidly cleared from the plasma by kidney, which makes the application of this polymer quite safe …”
Section: Resultsmentioning
confidence: 99%
“…The situation in the rat is of interest here, for Berglund and his colleagues (Berglund, 1964(Berglund, , 1965Berglund, Engberg, Persson &Ulfendahl, 1969) found that GFR decreased by about 30% as the molecular weight of the indicator substance increased from 400 to 6000 (Table 4). The point at which the clearance of polyethylene glycol became restricted in the rat was at a molecular weight of 4000 (Berglund, 1968) compared with 6000 in the dog (Shaffer, Critchfield & Carpenter, 1948).…”
Section: Renal Implicationsmentioning
confidence: 99%
“…The point at which the clearance of polyethylene glycol became restricted in the rat was at a molecular weight of 4000 (Berglund, 1968) compared with 6000 in the dog (Shaffer, Critchfield & Carpenter, 1948). Berglund (1964Berglund ( , 1965 concluded that inulin clearance gave an underestimate of GFR in the rat and attributed this to the small size of the glomerular pores in this species.…”
Section: Renal Implicationsmentioning
confidence: 99%
“…Measurement of renal clearance of inulin during constant infusion is still used as the reference method for estimation of GFR. The renal clearance of the inulin analogue polyfructosan does not differ from that of inulin clearance (Mertz, 1963) and has been used in a variety of experimental situations in man and animals (Berglund, 1965;Harth, 1963;Roch-Ramel, Chomety & Peters, 1968;Zender et al, 1964). In clinical practice, however, the constant infusion clearance method is less reproduceable than the single injection technique, since the latter does not need urine collection.…”
Section: Discussionmentioning
confidence: 99%